Improving Critical Thinking Skills Through Decision Making Learning Models in Pancasila and Citizenship Education Subjects - Dea Agnesti (International Journal of Students Education, 2024)
Education is things that are very important and what are not can free from life. Think critical is persistent efforts for test something to believe in the truth or knowledge with supporting evidence so that more carry on can taken correct conclusion. Skills think critical based on opinion a number of expert that is a habit for analyze, synthesize and evaluate information for solve a problem. Decision making is election decision or based policy on criteria certain. This study aim for explain how increase skills think critical student through learning models decision making on the eyes lesson education Pancasila and citizenship. Method used in this study is study bibliography. This study using secondary data form journal scientific, results study as well as books and other relevant sources. Data analysis techniques used covers three stages that is organizing, synthesizing, and identifying. Research result This show that learning model decision making on the eyes lesson education Pancasila and citizenship with stages including 1) identify problem, 2) looking for data for solution problem, 3) create conclusion, have relevance until indicator think critical covering interpretation, analysis, evaluation, and retrieval decision.